Atypical Pulmonary Eosinophilia Is Mediated by a Specific Amino Acid Sequence of the Attachment (G) Protein of Respiratory Syncytial Virus - Tebbey, Paul W. (The Rockefeller University Press, 1998)
We analyzed the immune responses evoked by a series of overlapping peptides to better understand the molecular basis for respiratory syncytial virus (RSV) G protein–induced eosinophilia in BALB/c mice. In vitro stimulation of spleen cells from natural G protein–primed mice showed dominant proliferative and cytokine (interferon [IFN]-γ and interleukin [IL]-5) responses to a peptide encompassing amino acids 184–198. Mice vaccinated with peptide 184– 198 conjugated to keyhole limpet hemocyanin showed significant pulmonary eosinophilia (39.5%) after challenge with live RSV. In contrast, mice immunized with a peptide (208–222) conjugate associated with induction of IFN-γ secreting spleen cells did not exhibit pulmonary eosinophilia after challenge. The in vivo depletion of CD4(+) cells abrogated pulmonary eosinophilia in mice vaccinated with the peptide 184–198 conjugate, whereas the depletion of CD8(+) cells had a negligible effect. Therefore, we have identified an association between peptide 184– 198 of natural G protein and the CD4(+) T cell–mediated induction of pulmonary eosinophilia after live RSV challenge. Out of 43 human donors, 6 provided peripheral blood mononuclear cells that showed reactivity to G protein from RSV A2, 3 of which responded to peptide 184– 198. The results have important implications for the development of a vaccine against RSV.